Whaling schooner A.T. Gifford in winter quarters, Hudson Bay, Canada - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1907)
View of the whaling schooner A.T. Gifford in winter quarters, west coast of Hudson Bay, Canada, ca. 1907-1912. People can be seen around the vessel, which appears to be banked with snow. Environment Infrastructure Livelihood Title supplied by cataloger. Information from original envelope identifies this as Photo # 23. The schooner A.T. Gifford was built in 1883 at Essex, Massachusetts. George Comer was her master during one of his Arctic voyages in which he mapped areas in the Hudson Bay area. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment.